Comparing measures of general and abdominal adiposity as predictors of blood pressure in college students. Issue 1 (2nd January 2018) - Abshire, Demetrius A.; Mudd-Martin, Gia; Moser, Debra K.; Lennie, Terry A.
ABSTRACT: Objective : To compare anthropometric measures of body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR), and sagittal abdominal diameter (SAD) as predictors of blood pressure in college students.Participants : Students ( N = 116) were recruited from November 2012 to May 2014 at an urban university and rural community colleges.Methods : Students underwent a brief physical examination during which anthropometric measures were obtained and blood pressure was measured. Covariates were measured using self-reported questionnaires. Hierarchical multiple linear regressions were used for the data analysis.Results : All anthropometric measures were predictive of systolic (SBP) and diastolic blood pressure (DBP). WC was the strongest predictor of SBP (β = .582, p < .01) explaining an additional 3–4% of the variance than BMI, WHtR, or SAD. The measures were similar in predicting DBP. WC predicted SBP independent of BMI.Conclusions : Clinicians should consider using WC to assess the risk for hypertension in college students.